Mary of Magdala : apostle and leader - Thompson, Mary R., 1928- (New York : Paulist Press, 1995)
Was the real Mary of Magdala a devoted disciple of Christ, a penitent, or a prostitute? Mary of Magdala: Apostle and Leader is a fascinating examination of the actual written accounts referring to Mary. The result is a portrait of the various images of Mary of Magdala that have emerged in different guises over the centuries.
I. The Background -- II. Scriptural Evidence -- III. Mary of Magdala in Mark and Matthew -- IV. Mary of Magdala in Luke -- V. Mary of Magdala in the Fourth Gospel -- VI. Women Leaders in the Ancient World -- VII. Women in the Apocryphal and Canonical Literature -- VIII. Conclusions -- Epilogue: Mary as Role Model.
Includes bibliographical references (p. 138-143) and index.
Keywords: Mary Magdalene, -- Saint; Mary Magdalene, -- Saint -- Cult -- History